Risk identification of heavy metals in well water surrounds watershed area of Pangkajene, Indonesia - Ratna Dwi Puji Astuti; Anwar Mallongi; Ridwan Amiruddin; Muhammad Hatta; Annisa Utami Rauf (Elsevier, 2021)
Objective: This study wants to evaluate heavy metals pollution and ecological risk level of well water in Pangkajene watershed area. Methods: The total concentration of Cd, Cr(VI), Pb and Ni were determined using AAS. We used heavy metal pollution index (HPI), metal index (MI), hazard quotient (HQ) used to estimate metals pollution and ecological risk level. Pearson correlation analysis is executed to evaluate the relationship between all measured parameters. Result: The concentration of Cd, Ni and Pb are below detection limit value. The mean concentration of Cr(VI) 0.0017 ± 0.0006 mg L−1. The mean of HPI and MI value are 3.06 and 0.06, respectively. The upstream area of Pangkajene has HQ value for Cr(VI) is higher than 1, it indicates that exposure of Cr(VI) may cause adverse effects to the ecological system and human health. Conclusion: The Cr(VI) is the main risk factor for well water contamination surrounds Pangkajene watershed area.